Seismic Assessment and Proposal for Interventions of a Historical Masonry Building in Rhodes - Eleftheriou, Andromachi; Papachristidis, Aristidis; Repapis, Constantinos (Technical Annals, 2024)
The aim of this study is the seismic assessment of a historical two-storey masonry building, located in the city of Rhodes and the investigation of intervention ways to strengthen the building and improve the mechanical characteristics of its materials. The 3DR.PESSOS software was used for the simulation and analysis of the structure. For the evaluation of the seismic behaviour of the building, an elastic static analysis (lateral force analysis) was carried out based on the Greek Code for Structural Interventions of Masonry Structures. Elastic static analysis methods with global behaviour factor (q) or local ductility indices (m) were applied for performance levels B1 and B2. From the analyses and the code checks it was concluded that the building is vulnerable to in-plane and out-of-plane actions. For this reason, methods of intervention are being investigated to increase the diaphragm function of the building and to improve the mechanical characteristics of the masonry.